THE INFLUENCE OF GOOD CORPORATE GOVERNANCE AND ENVIRONMENTAL SOCIAL GOVERNANCE ON FINANCIAL PERFORMANCE - Risma Haris Nuriyanti; Aisha Hanif (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study aims to analyze the influence of Good Corporate Governance and Environmental Social Governance on Company Financial Performance. Method: The population taken in the study is companies listed on the Indonesia Stock Exchange (IDX) in 2018-2023, which are included in the ESG Star Listed Companies because they have annual reports and sustainability reports, and are developed with the GRI standard. The sample taken in this study used purposive sampling and data analysis technique using multiple linear regression and tested using SPSS Software. Results: The results of the study indicate that GCG with independent commissioner indicators has an effect on financial performance, while the audit committee and ESG have no effect on financial performance proxied by NPM (Y). Novelty: This study shows that GCG is very important to be implemented continuously in companies using GCG, while ESG, in the study, although very important for the sustainability of the company, does not have a positive effect.